Endolysin significantly improves symptoms with atopic dermatitis: bridging the gap from research to clinical practice - Kui, Ling; Huang, Jinqun; Wang, Guoyun; Zhao, Jiamin; Wang, Shuangshuang; Qin, Xiaoxing; Liu, Leifeng; Hu, Jianfei; Chen, Lianjia; Wang, Xingchun; Li, Qing; Zhao, Yuqian; et al. (Frontiers in Immunology, 2025)
BackgroundAtopic Dermatitis (AD), a chronic inflammatory skin disease characterized by pruritus, dryness, redness, edema, scratching, and lichenification, ranks as the leading cause of non-fatal skin disease burden globally. Current therapeutic strategies for AD primarily act by inhibiting inflammatory pathways, yet largely fail to address Staphylococcus aureus (S. aureus) control unless exudative lesions are present. However, concerns over treatment-related adverse effects, long-term safety profiles, and emerging drug resistance underscore the remaining substantial unmet clinical needs in this field.ObjectivesTo evaluate the safety and efficacy of endolysin gel in treating AD.MethodsAn infection-driven dermatitis model with AD-like features was established. Following treatment with Staphyrase® or in other control groups, skin disease severity scores, S. aureus CFU, and key inflammatory cytokines were assessed. An open-label, single-center, investigator-initiated clinical study (ChiCTR25001192) was conducted in which participants, who received the endolysin gel twice daily, underwent follow-up assessments at baseline, treatment weeks 1 and 2, with an optional extension up to 3 months.ResultsStatistically significant reductions in skin lesion scores, S. aureus load, and AD-related immune mediators (i.e., IgE, TSLP, IL-33) were observed in the Staphyrase® group relative to the model group. All 20 enrolled adult subjects completed the clinical study, with no tolerability issues reported, indicating a favorable safety profile of the endolysin gel. Compared to baseline, EASI, SCORAD, IGA, VAS, and DLQI scores demonstrated significant decreases at both Day 7 and Day 14 (all P < 0.05). Notably, Participant No. 11, who underwent extended follow-up until Week 8, exhibited substantial improvements in redness, lichenification, severe scratching, oozing, and dryness. The Endolysin gel showed consistent safety and efficacy in improving both acute and chronic AD lesions.ConclusionsTopical endolysin gel is a well-tolerated, effective, and promising agent for the treatment and proactive maintenance of mild-to-moderate AD in adults.